2022
DOI: 10.3389/fimmu.2022.837977
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 Inhibition Attenuates Inflammatory Pain by Ameliorating NLRP3 Inflammasome-Induced Pyroptosis

Abstract: Chronic pain, such as persistent inflammatory pain, remains a public health problem that has no effective treatment at present. Bromodomain-containing protein 4 (BRD4) inhibition, induced by JQ1 injection or BRD4 knockdown, has been used to attenuate inflammatory pain; However, it remains elusive whether BRD4 aggravates inflammatory pain by regulating inflammasome. Western blot and immunofluorescence staining showed that BRD4 expression increased after administration of complete Freund’s adjuvant (CFA) and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…Michoud et al study showed that direct stimulation of neurons using optogenetics without additional damage can also lead to neuroinflammation [39]. Hua et al also found that activation of NLRP3 and caspase-1 in neurons can also lead to neuroinflammation [40]. NLRP3 has been found to be significantly elevated in neurons [41] and microglia [42] in the epileptic brain, which is mainly stimulated by intracellular environment and cell membrane receptor signals [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Michoud et al study showed that direct stimulation of neurons using optogenetics without additional damage can also lead to neuroinflammation [39]. Hua et al also found that activation of NLRP3 and caspase-1 in neurons can also lead to neuroinflammation [40]. NLRP3 has been found to be significantly elevated in neurons [41] and microglia [42] in the epileptic brain, which is mainly stimulated by intracellular environment and cell membrane receptor signals [43].…”
Section: Discussionmentioning
confidence: 99%
“…The NLRP3 inflammasome is a protein complex that promotes the release of inflammatory factors in response to infection or tissue injury and is known to be associated with many nervous system diseases, such as Alzheimer's disease (AD), depression and epilepsy [39][40][41]. The role of NLRP3 in neuroinflammation in combination with its broad range of mediators indicates that GPR120 might regulate neuroinflammation and manifest its protective effect in epilepsy through NLRP3-dependent signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory pain is evoked by inflammation-associated stimuli and is often established in animal models using wound incision or injection of inflammatory chemical irritants, such as complete Freund’s adjuvant (CFA), carrageenan or lipopolysaccharides (LPS) ( Pan et al, 2021 ). Recent literatures have demonstrated that intraplantar administration of complete Freund’s adjuvant (CFA) or ceramide not only down-regulates paw withdrawal mechanical threshold and paw withdrawal thermal latency, but also up-regulates the expression of the NOD-like receptor protein 2 (NLRP2)/caspase-1/IL-1β in small-sized DRG primary sensory neurons and the generation of NLRP3/caspase-1 in spinal dorsal horn neurons ( Matsuoka et al, 2019 ; Hua et al, 2022 ). Intrathecal injection of a caspase-1 inhibitor Z-YVAD-FMK impairs CFA-induced inflammatory pain hypersensitivity through inhibiting IL-1β secretion in DRG ( Matsuoka et al, 2019 ).…”
Section: Caspases and Inflammatory Painmentioning
confidence: 99%
“…Moreover, we also used adjusted Aging-GIP1, where the effects on human lifespan and healthspan that are correlated with socioeconomic status are removed. We showed that after adjusting for socioeconomic status, the CpG site with the top pro-longevity effect is cg06636172 at the FOXO locus, which is a major longevity locus 36,37 .…”
Section: Epigenome-wide Mendelian Randomization On Aging-related Phen...mentioning
confidence: 94%